2018
DOI: 10.1111/ctr.13292
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in transplantation: Written off or comeback with novel indication?

Abstract: Renal-dose dopamine has fallen out of favor in the intensive care unit (ICU) during past years due to its ineffectiveness to prevent impending or to ameliorate overt renal failure in the critically ill. By contrast, growing evidence indicates that low-dose dopamine administered to the stable organ donor after brain death confirmation improves the clinical course of transplanted organs after kidney and heart transplantation. Ensuring a thorough monitoring for potential circulatory side effects, employment of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
5
1
3
Order By: Relevance
“…In conclusion, this study demonstrates that the use of low‐dose dopamine at 4 µg/kg/minute in hemodynamically stable donors is safe in LT, and therefore, its use as a standard of care is warranted because it benefits other organs, kidneys, and hearts, without deleterious effects in liver allografts.…”
Section: Discussionmentioning
confidence: 76%
“…In conclusion, this study demonstrates that the use of low‐dose dopamine at 4 µg/kg/minute in hemodynamically stable donors is safe in LT, and therefore, its use as a standard of care is warranted because it benefits other organs, kidneys, and hearts, without deleterious effects in liver allografts.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, and supporting a notion that CIT length may influence the efficacy of MP, the MP trial investigators found in a recent post hoc analysis that the effect on DGF was largest for kidneys exposed to CIT <10 hours. [30][31][32][33] Dopamine's effectiveness requires diffusion into cells, 34 which under the steadystate conditions of continuous infusion is a time-dependent process. One also needs to bear in mind that any donor organ treatment administered before organ procurement will affect the outcome of two kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms conferring kidney protection by dopamine are not related to circulatory effects but rather depend on dopamine's antioxidant properties. [30][31][32][33] Dopamine's effectiveness requires diffusion into cells, 34 which under the steadystate conditions of continuous infusion is a time-dependent process.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Donörde yeterli sıvı replasmanına rağmen hipotansiyon devam ediyorsa vazopressör olarak ilk planda düşük doz dopamin infüzyonu önerilmektedir. [12][13][14] Dopamine alternatif olarak veya ek vazopressör ihtiyacı mevcutsa vazopressin ve noradrenalin kullanılabilir. 13,15 Düşük doz dopamin infüzyonunun (4 µg/kg/dk) beyin ölümü deklarasyonundan hemen sonra başlanması gerektiği ve donörlerde güvenlice uygulanabileceği tavsiye edilmiştir.…”
Section: Introductionunclassified
“…Donöre uygulanan düşük doz dopamin infüzyonunun (4 µg/kg/dk) süresi (kros klemp konuncaya kadar) 7 saat ve üzerinde olduğunda organ transplantasyonundan sonra nakledilen organların klinik seyirlerini iyileştirdiği bildirilmiştir. 14,16,17 Donöre uygulanan düşük doz dopamin infüzyonunun böbrek transplantasyonundan sonra diyaliz ihtiyacını azalttığı, 14,18 kalp transplantasyonlarında da hastanın kliniğini iyileştirdiği gösterilmiştir. 17,19 Bu bilgiler ışığında hastanemizde donör bakımında standart olarak tüm donörlere 4 µg/kg/dk dopamin infüzyonu, metilprednizolon infüzyonu ve levotiroksin uygulanmıştır.…”
Section: Introductionunclassified